Image Informative Maps for Estimating Noise Standard Deviation and Texture Parameters. (14th March 2011) - Uss Uss, M. M.; Vozel Vozel, B. B.; Lukin Lukin, V. V.; Abramov Abramov, S. S.; Baryshev Baryshev, I. I.; Chehdi Chehdi, K. K.
Abstract : The problem of automatic detection of image areas appropriate for accurate estimation of additive noise standard deviation (STD) irrespectively to processed image properties is considered in this paper. For accurate estimation of either image texture or noise STD, we distinguish two complementary informative maps: noise- (NI-) and texture- (TI-) informative ones. The NI map is determined and iteratively upgraded based on the Fisher information on noise STD calculated in scanning window (SW) fashion. Fractional Brownian motion (fBm) model for image texture is used to derive the required Fisher information. To extract final noise STD from NI map, fBm- and DCT-based estimators are implemented. The performance of these two estimators is comparatively assessed on large image database for different noise levels. It is also compared with performance of two competitive state-of-the-art estimators recently published. Utilizing NI map along with DCT-based noise STD estimator has proved to be significantly more efficient.